Medical authority and ordinary expertise: The changing forms of doctors' talk in Swedish public service television 1983–2013. (September 2016) - Ekström, Mats
Abstract: Expertise is frequently performed in the broadcast media. While academic expertise is typically promoted in expert news interviews (Montgomery, 2007), a questioning of expert authorities at the expense of lay discourses is a feature of several talk show formats (Livingstone and Lunt, 1994 ). This study analyses how doctor׳s expertise is performed in broadcast media, with a focus on "the in-house doctors". These are doctors who claim expertise as representatives of an academic profession and are affiliated as key actors (not occasional guests) in broadcast productions. More specifically, this study explores in-house doctors, and the changing forms of doctors׳ expertise performed in different genres of talk in three studio-based magazine programs from 1983 to 2014. The study shows a shift from the traditional medical authority performed in expert interviews and monologues of lecturing style (in the 1980s), to in-house expertise shaped by its orientation towards a communicative ethos and conversational qualities described in terms of the ordinariness of broadcast communication. The latter is mainly demonstrated in detailed analyses of the very successful show Ask the Doctor broadcast weekly since 2003 and with over one million viewers. In the show, the in-house doctor answers questions from viewers׳ letters. The analyses show how the doctor׳s performed expertise and epistemic status are reshaped in relation to: (1) the genres of talk used in the broadcast production; (2) the sense of inclusion in talk and gaze and use of personal forms of address, (3) the design of beneficial and responsible diagnoses and advice for the particular participant framework, (4) orientation toward both medical expertise, everyday experiences and lay knowledge.